Ethics of Hadith-Based Digital Islamic Communication: A Literature Study of Its Principles and Urgency in the Modern Era - Riki Janwir Hidayat; Nasrulloh Nasrulloh (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
Departing from the increasing dynamics of religious communication in the digital space which is often characterized by information distortion, polarization, and abuse of religious authority, this study aims to formulate an ethical framework for digital da'wah based on hadith by utilizing the analysis of the principles of communication ethics according to Johannesen. The study uses a library research method through the search for normative hadiths related to speech, information delivery, and the moral responsibility of communicators, which are then analyzed qualitatively through a content approach and contextualized with Johannesen's principles of communication ethics, such as truthfulness, respect, harm-avoidance, responsibility, empathy, justice, and ethical freedom. The results of the study show that the hadiths on the obligation to speak the truth, the prohibition on spreading unverified information, the recommendation to speak well or remain silent, warnings against abuse of authority, as well as the principles of non-polarization and maintaining social harmony provide a strong normative basis for formulating digital da'wah ethics that are relevant to the challenges of modern communication ecology. The integration of hadith and Johannesen's theory emphasizes that communication ethics must avoid provocative rhetoric, antagonistic framing, and sectarian narratives, and instead prioritize information verification, polite communication, transparency of da'wah intentions, audience protection from manipulation, moral responsibility for social impacts, and a commitment to maintaining social cohesion as a communal good. This study concludes that the integration of hadith values ​​and modern communication ethics can provide authoritative, adaptive, and constructive digital da'wah guidelines for Islamic preachers and content creators.